THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON CUSTOMER LOYALTY: A LITERATURE REVIEW - Amândio de Araújo Sarmento (CV. Adiba Aisha Amira, 2024)
This study examines the effect of corporate social responsibility (CSR) on customer loyalty through a literature review of various previous studies. The findings show that CSR has a positive and significant impact on customer loyalty. When companies demonstrate their commitment to social and environmental issues, this increases customers' positive perceptions, which in turn encourages their loyalty. Active customer participation in CSR initiatives also strengthens emotional connections and increases attachment. In addition, transparency and effective communication about CSR activities have been shown to strengthen customer trust and loyalty. Overall, the integration of CSR in a company's business strategy and active engagement with customers play an important role in creating and maintaining customer loyalty.